Cohort study of Gorlin syndrome with emphasis on standardised phenotyping and quality of life assessment. Issue 6 (June 2017) - Huq, Aamira J.; Bogwitz, Michael; Gorelik, Alexandra; Winship, Ingrid M.; White, Susan M.; Trainer, Alison H.
Abstract : Background: Gorlin syndrome (nevoid basal cell carcinoma syndrome) is a rare genetic predisposition to basal cell carcinomas (BCC), keratocysts of the jaw and calcification of the falx cerebri among other clinical features. With the advent of sonic hedgehog inhibitors for the treatment of BCC, it is timely to establish a cohort of individuals with Gorlin syndrome and collect standardised phenotypic information on these individuals. Moreover, the health‐related quality of life (QoL) in individuals with Gorlin syndrome is not well studied. Aim: To establish a Victorian cohort of Gorlin syndrome and study the QoL in these individuals. Methods: Phenotypic data were obtained by reviewing medical records of individuals attending two major tertiary/quaternary genetic referral centres in Victoria, followed by telephone or face‐to‐face interviews where possible. QoL information was obtained utilising the AQoL‐6D quality of life survey form. Results: The median number of BCC in the 19 individuals studied was 17.5 (interquartile range 3–70). The number of patients with ≥100 BCC in this group was similar to a previously described national cohort (22.2 vs 27% respectively). A total of 58% of referrals to the genetics clinics originated from maxillofacial surgeons and 42% from dermatologists. Individuals with ≥100 BCC had worse median QoL scores compared to those with <100 BCC (36 vs 29, P ‐value of 0.031). Conclusion: The clinical features in our cohort were congruent with those previously described in Australia. The QoL is adversely correlated with increased BCC burden.